2015
DOI: 10.1007/s11739-015-1319-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of heart failure with preserved ejection fraction in patients with an exacerbation of chronic obstructive pulmonary disease

Abstract: Diagnosing heart failure with preserved ejection fraction (HFpEF) in patients with chronic obstructive pulmonary disease (COPD) is difficult due to overlapping pathophysiological pathways, risk factors and clinical presentations. We investigated the prevalence and prognostic implications of coexisting HFpEF in patients hospitalized for acute exacerbation of COPD. A total of 116 consecutive patients with an acute exacerbation of COPD were evaluated for HFpEF and followed for an average period of 22 ± 9 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…It should be underlined, however, that our study cannot determine whether the association between diastolic dysfunction and mortality in COPD patients differs from the usual association in patients with cardiac disease, because all patients had COPD. We have recently shown that elevated N‐terminal pro B‐type natriuretic peptide levels were independently associated with unfavorable overall survival in patients with an exacerbation of COPD, whereas heart failure with preserved ejection fraction, as a surrogate marker for LV diastolic dysfunction, was not …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be underlined, however, that our study cannot determine whether the association between diastolic dysfunction and mortality in COPD patients differs from the usual association in patients with cardiac disease, because all patients had COPD. We have recently shown that elevated N‐terminal pro B‐type natriuretic peptide levels were independently associated with unfavorable overall survival in patients with an exacerbation of COPD, whereas heart failure with preserved ejection fraction, as a surrogate marker for LV diastolic dysfunction, was not …”
Section: Discussionmentioning
confidence: 99%
“…Last, our study evaluated prognostic implications of echocardiographic parameters only, adjusted for age and COPD severity. We recently reported on the prognostic implications of echocardiographic parameters within the context of heart failure with preserved ejection fraction and COPD . However, further multicenter, large‐scale studies with adequate statistical power are needed to elucidate the predictive value of echocardiographic parameters in the presence of other factors known to influence long‐term survival in patients with COPD.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that systemic inflammation, pulmonary vasoconstriction, and polycythemia and endothelial dysfunction expose COPD patients to pulmonary hypertension, the therapeutic option which attenuates PAP can improve dyspnea score. In our study 12 (60%) patients in the verapamil group and 11 in the placebo group (55%) had a PAP higher than 35 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…One key candidate is the heterogeneous nature of exacerbations, which can be triggered by myriad factors. Approximately half of exacerbations have been associated with bacterial infections by culture-dependent techniques and nearly 60% with viral infections (36), but some exacerbations may be triggered by air pollution (37), changes in temperature and barometric pressure (38,39), and possibly shifts in intrapulmonary fluids in those with occult heart failure (40). From this viewpoint, the inability to identify reproducible biomarkers follows inability to classify the etiology for each exacerbation accurately.…”
Section: Discussionmentioning
confidence: 99%